2006
DOI: 10.1007/s00405-005-0003-9
|View full text |Cite
|
Sign up to set email alerts
|

A five-week-old girl with inspiratory stridor due to infantile hemangiopericytoma

Abstract: Infantile hemangiopericytoma is a rare tumour of infancy and a very rare cause of inspiratory stridor in this age group. The mainstay of treatment is surgery. The overall prognosis is favourable but because of the unpredictable nature of the tumour, long-term follow-up is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…There is no ideal chemotherapy regimen , but the most commonly used drugs are vincristine, actinomycin D, cyclophosphamide, methotrexate, doxorubicin, prednisone, and dacarbazine .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no ideal chemotherapy regimen , but the most commonly used drugs are vincristine, actinomycin D, cyclophosphamide, methotrexate, doxorubicin, prednisone, and dacarbazine .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors believe that it originates from Zimmermann's vascular pericytes, which are contractile fusiform cells that surround capillaries and postcapillary venules , but the exact origin of the lesion is unclear. Given that the clinical and pathologic features overlap with those of myofibromatosis and solitary fibrous tumor (SFT), it has been suggested that these three entities are related variants of a continuous spectrum and that their histologic characteristics may correspond to different stages of maturation . Infantile myofibromatosis often has a marked biphasic pattern with an area of plump spindle cells arranged in short fascicles and an area of more round or oval cells around blood vessels, whereas HPC has a greater prominence of oval cells around blood vessels .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation